3.3 kV/1 800 A IGBT Module with Advanced Trench HiGT Structure and Its Module Design Optimization - Takayuki Kushima; Katsunori Azuma; Yasuhiro Nemoto; Katsuaki Saito; Yoshihiko Koike (Kongzhi Yu Xinxi Jishu)
Hitachi developed a 3.3 kV/1 800 A IGBT module with the highest current rating, whose current rating would be increased by 20% compared with the conventional type products, which had the same size and voltage level. The advanced trench HiGT structure was used to achieve low loss, and the electrical and thermal designs were optimized in order to reduce thermal resistance and parasitic inductance.